2014
DOI: 10.3920/bm2013.0001
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double-blind placebo-controlled study of the effect of Lactobacillus paracasei NCC 2461 on skin reactivity

Abstract: In recent decades, the prevalence of subjects with reactive skin has considerably increased in industrialised countries. 50% of women and 30% of men report cutaneous discomfort classified under reactive/sensitive skin. Several topical approaches have been proposed, in particular through improvement of galenic forms or protection of epidermal surface. We propose to act differently, deeply from inside the body via an innovative nutritional approach. To this purpose, Lactobacillus paracasei NCC 2461 (ST11) was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 24 publications
4
59
0
1
Order By: Relevance
“…These observations raise hope that the right kind of bacteria may have beneficial effects on the skin homoeostasis, skin inflammation, and peripheral tissue responses to perceived stress. Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83].…”
Section: Resultssupporting
confidence: 60%
“…These observations raise hope that the right kind of bacteria may have beneficial effects on the skin homoeostasis, skin inflammation, and peripheral tissue responses to perceived stress. Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83].…”
Section: Resultssupporting
confidence: 60%
“…In most cases, due to formulation challenges, much research has been performed using probiotic lysates (postbiotics) (mechanical, chemical or heat‐killed bacteria) with positive results . However now, with more data and information available on how bacteria can influence the skin in health and disease, there has been increased research activities on topical live products particularly in the areas of sensitive skin and more complex skin disorders such as acne and atopic dermatitis (AD) …”
Section: Discussionmentioning
confidence: 99%
“…Thus, collectively the effect of pro‐ and postbiotics of L. reuteri DSM 17938 could be considered as complementary in terms of skin barrier improvement. Previous clinical studies demonstrated that the combined application of L. paracasei and Bifidobacterium longum lysate is effective for treating “sensitive skin” such as dry/irritated skin, while another study reported increased barrier resistance, reduced skin sensitivity and dryness in patients with reactive skin by the topical treatment of B. longum lysate . Thus, the live and lysate product of L reuteri DSM 17938 could be further evaluated for treatment of sensitive/irritated skin and dehydrated skin condition.…”
Section: Discussionmentioning
confidence: 99%
“…Oral ingestion of certain probiotic strains has been shown to improve the skin barrier and affect skin hydration and transepidermal water loss. Gueniche et al (2014) studied the effects of oral supplementation with L. paracasei NCC2461 versus placebo for healthy female volunteers via a randomized placebo-controlled clinical trial. A capsaicin test was used to monitor skin sensitivity, while transepidermal water loss and dermatological assessments were utilized to measure skin barrier function.…”
Section: Immune Regulationmentioning
confidence: 99%